1994
DOI: 10.3109/00048679409075868
|View full text |Cite
|
Sign up to set email alerts
|

Parental Representation in Suicidal Adolescents: A Controlled Study

Abstract: One hundred and eighty-seven adolescents referred to outpatient and residential services in three Canadian cities were assessed for lifetime suicidal ideation and attempt, and administered the Parental Bonding Instrument (PBI). Suicidal adolescents of both genders reported lower care and higher over-protection in relation to their mothers than non-suicidal subjects, and female subjects reported this pattern for their fathers as well. Male subjects did not show clear differentiation between groups on PBI rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 27 publications
2
34
1
Order By: Relevance
“…Adolescent studies using the Parental Bonding Instrument (PBI; Parker, Tupling, & Brown, 1979), a measure of perceived parenting style, show that subjects who perceive their parents as uncaring and/or overprotective are at increased risk for suicidal ideation and behavior (Adam, Keller, West, Larose, Goszer, 1994;Martin & Waite, 1994). These studies demonstrate the utility of the PBI and the FAD in distinguishing suicidal adolescents in both clinical and nonclinical samples.…”
Section: Contextual Risk Factorsmentioning
confidence: 87%
“…Adolescent studies using the Parental Bonding Instrument (PBI; Parker, Tupling, & Brown, 1979), a measure of perceived parenting style, show that subjects who perceive their parents as uncaring and/or overprotective are at increased risk for suicidal ideation and behavior (Adam, Keller, West, Larose, Goszer, 1994;Martin & Waite, 1994). These studies demonstrate the utility of the PBI and the FAD in distinguishing suicidal adolescents in both clinical and nonclinical samples.…”
Section: Contextual Risk Factorsmentioning
confidence: 87%
“…Kandel, Raveis, and Davies (1991) noted that suicidal ideators were less close to their parents. Adam, Keller, West, Larose, and Gozner (1994) reported that in adolescent girls, suicidal ideation was related to low care and high overprotection by both parents, whereas in boys ideation was associated with low care and high overprotection by their mothers only. De Man and Leduc (1994) noted greater suicidal ideation among adolescents coming from controlling family backgrounds.…”
mentioning
confidence: 94%
“…Certain combinations of maladaptive parental behaviors, such as affectionless and overprotective parenting, have been reported to be associated with risk for suicide. [19][20][21] Research has indicated that suicidal behavior tends to be ORIGINAL ARTICLE multidetermined 2 and that individuals who are exposed to a series of adversities during childhood and adolescence are at a particularly elevated risk for suicide. 19,22 Developmental theorists have hypothesized that negative life events and interpersonal difficulties may play an important role in determining whether childhood…”
mentioning
confidence: 99%